Parasitological and serological detection of Trypanosoma evansi on Bali cattle at the Pesanggaran slaughterhouse, Denpasar, Indonesia using hematological profile - IDA AYU PASTI APSARI; NYOMAN ADI SURATMA; IDA BAGUS NGURAH SWACITA; I GEDE SOMA; TRI KOMALA SARI; I PUTU CAHYADI PUTRA; PUTU HENRYWAESA SUDIPA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Apsari IAP, Suratma NA, Swacita IBN, Soma IG, Sari TK, Putra IPC, Sudipa PH. 2024. Parasitological and serological detection of Trypanosoma evansi on Bali cattle at the Pesanggaran slaughterhouse, Denpasar, Indonesia using hematological profile. Biodiversitas 25: 1057-1062. Bali cattle (Bos sondaicus Blyth, 1842 syn. Bos javanicus domesticus Wilckens, 1905) are vulnerable to blood protozoan infections like Trypanosoma evansi. Indonesia's warm and moist environment provides ideal conditions for blood-sucking flies such as Stomoxys calcitrans, Haematobia irritans, and Hipobosca sp. to thrive and spread. These flies act as carriers of T. evansi, which can then infect Bali cattle. This study aims to detect the presence of T. evansi in Bali cattle. Blood samples were collected from 275 Bali cattle at the Pesanggaran slaughterhouse, Denpasar City, Bali, Indonesia. The samples were examined using the Giemsa-Staining Blood Smear (GSBS) method and hematology profile examination using Hematology Analyzer RT-7600 for Vet. Serum samples were also collected for serologic examination using the Card Agglutination Test for Trypanosomiasis (CATT) method. The hematological profile data obtained were analyzed descriptively, and the Mann-Whitney U test was used to determine the significance of hematological values between female and male cattle seropositive to T. evansi. The results showed that the T. evansi parasite was not detected in the blood smear examination. However, the serological detection with CATT revealed that 6.54% (18/275) of Bali cattle were positive for T. evansi. The hematological profiles of T. evansi seropositive cattle remained within the normal range, except for neutrophil percentage. White Blood Cell (WBC), Hemoglobin (Hb) levels, and hematocrit (PCV) values of male cattle were significantly (P?0.05) lower than those of females. Therefore, based on serological examination, it can be concluded that the protozoa T. evansi is present in 6.54% of Bali cattle at the Pesanggaran slaughterhouse.